A stall-regulated wind turbine design to reduce fatigue. (April 2019) - Macquart, Terence; Maheri, Alireza
Abstract: Variable-speed stall-regulated (VS-SR) wind turbines can be designed to produce power as efficiently as variable-speed pitch-controlled (VS-PC) systems. However, amongst the main drawbacks of VS-SR systems high transient power and low predictability have been the primary factors in favour of adopting VS-PC system for multi-MW wind turbines. Cyclic and stochastic loads leading to fatigue failure is one of the prime considerations for large wind turbines. In contrast to the current trend of research, which is focused on load alleviation by integrating active flow controllers, this paper highlights the potential benefits of VS-SR wind turbines in reducing fatigue loads. Adopting the NREL 5 MW wind turbine as the baseline, blades are redesigned for stall-regulation. It is shown that a well-designed VS-SR wind turbine experiences significantly less fatigue loads compared to VS-PC systems. It also results in low power transients near and above rated wind speed. Taking into account added complexity, mass and maintenance costs of wind turbines utilising active flow controllers and in view of the recent progresses that have been made regarding the aeroelastic stability of stalled blades, VS-SR systems seem to have a role to play in the design of future wind turbines. Highlights: The potentials of variable speed stall regulated multi-MW wind turbines in shown. Aerodynamic insensitivity of stalled blades is utilised to reduce fatigue loads. Power well-maintained at rated value while operating under highly turbulent winds. Progressive stall line is a new parameter used for planning aerodynamic sensitivity.